MODEL SIMULASI UNTUK PENYELESAIAN PROBLEM INTEGRASI PRODUKSI-DISTRIBUSI - Annisa Kesy Garside (Jurnal Gamma, 2009)
The analyticalmodel to solve the integration-production-distribution problem has drawbackof not able to accomodate the uncertainty of supply chain. This research aims to develop a simulationmodel to obtain a production and distribution plan that not only minimize the production anddistribution cost but also implementable in the real world situation.The steps of the research includes data generation, analytical model formulation and solutionmodel search, deterministic simulation model design based on generated data and analytical solutionmodel, verification test, running deterministic simulation model, validation test, stochastic simulationmodel design by incorporating uncertainty factor in terms of probabilistic production time andvehicle speed and validation of analytical solution model to determine whether the analytical modelsolution is worth to be implemented.The deterministic simulation and stochastic models were designed with ARENA simulationsoftware. Based on the stochastic running model, the total time for period one is higher than 48available hours so concluded that analytical solution model is not worth implemented.Keywords:. supply chain, production-distribution integration, analytical model, simulation model,deterministic, stochastic, ARENA software